Perfil e teores de aminas bioativas em frutas brasileiras - Flavia Mendes de Faria (2011)
The types and levels of ten bioactive amines and some physico-chemical characteristics were determined in tem Brazilian fruits, among them, avocado, açaí, cajá-manga, caqui, carambola, graviola, jenipapo, pequi, pear and umbu. The fruits were from the market of Belo Horizonte, state of Minas Gerais, Brazil, from March of 2010 until January of 2011; except for açaí which was provided by Universidade doPará, Belém, PA. The fruits had pH, soluble solids and total titratable acidity characteristics of the species. Among the ten amines investigated, five were detected - spermidine, spermine, putrescine, tyramine and cadaverine. Graviola was the fruit with the larger diversity of amines (all Five), avocado and pequi had four amines, açaí, caqui, carambola and umbu had three and the remaining fruits had two (spermidine andputrescina). Spermidine was detectede in every sample analyzed, followed by putrescine (81%), spermine (38%), tyramine (23%) and cadaverine (16%). The median levels of total amines varied from 0.47 mg/100 g in caqui to 1.37 mg/100 g in avocado. With regards to the polyamines, avocado and cajá-manga were the best sources (0.95and 0.69 mg/100 g, respectively). Açaí was the fruit with higher spermine levels (0.39 mg/100 g). These three fruits are the ones with higher antioxidant potential. Tyramine was present in 100% of the graviola and umbu samples. These fruits should be avoided by individuals under mono aminoxidase inhibitor drugs. There was significantcorrelation between the physico-chemical characteristics and the amines investigated.